Evaluating antimicrobial activity of selected medicinal plant extracts against pasteurellosis-causing bacteria in small ruminants - Asfa, Beshada; Woldemichael, Dereje Nigussie; Tesfaw, Liyuwork; Asefa, Lishan; Desta, Solomon; Girma, Sisay; Tolera, Teshale Sori; Tufa, Takele Beyene (Frontiers in Veterinary Science, 2025)
Pneumonic pasteurellosis is a highly significant infectious disease globally, posing a major economic threat to small ruminants (SR) in Sub-Saharan Africa, including Ethiopia. Although antibiotics have been effective in treating this disease, farmers in remote areas of Ethiopia often prefer traditional herbal medicines to manage respiratory infections in SR. This study aimed to evaluate the antibacterial activity of crude extracts from three selected medicinal plants—Nicotiana tabacum, Psidium guajava, and Solanum incanum—against respiratory infections caused by Pasteurella multocida and Mannheimia haemolytica in SR, in comparison to commercial gentamicin, oxytetracycline, and streptomycin antibiotics. The Agar well diffusion method was used to determine the antibacterial activity of methanol and chloroform extracts from the three medicinal plants against P. multocida and M. haemolytica strains. The phytochemical constituents of the plant extracts were analyzed by using standard phytochemical screening methods. Methanol extracts from all three plants demonstrated significant antibacterial activity against both bacterial strains (Pasteurella multocida and Mannheimia haemolytica) at a concentration of 200 mg/mL, comparable to the effectiveness of gentamicin and streptomycin. Among the three plants, S. incanum showed the highest zone of inhibition (26.3 mm), followed by N. tabacum (19.8 mm) and P. guajava (19.6 mm) against the tested strains. Similarly, chloroform extracts also exhibited notable activity, with P. guajava showing the highest inhibition (30.2 mm) against P. multocida at 200 mg/mL. Phytochemical screening revealed the presence of various bioactive compounds, including alkaloids, flavonoids, tannins, saponins, and terpenoids. These findings support the traditional use of these medicinal plants in treating respiratory infections caused by P. multocida and M. haemolytica in SR.